Atroposelective Synthesis of Tetrahydropyrrolo[3, 2‐c]azepine Derivatives Through Gold(I)‐Catalyzed Hydroarylation. Issue 24 (29th November 2022) - Gaignard‐Gaillard, Quentin; Han, Xu; Alix, Aurélien; Bour, Christophe; Guillot, Regis; Gandon, Vincent; Voituriez, Arnaud
Abstract: A series of enantioenriched substituted tetrahydropyrrolo[3, 2‐ c ]azepine products possessing an axial chirality were synthesized in 63–99% yield through a gold(I)‐catalyzed hydroarylation. DFT calculations rationalized the reactivity observed for the formation of such complex molecular frameworks and guided our choice in the pyrrole N ‐substituent to isolate configurationally stable compounds. Abstract :